Pandangan Ibnu Hazm Al-Andalusi tentang Etika Religius dan Aktualisasinya dalam Pendidikan - Abdul Khobir (Edukasia Islamika, 2017)
This present study aims to describe the religious ethics and its actualization in todayâ€™s education system according to Ibn Hazm. A qualitative approach was employed in this library research. The data sources consist of primary and secondary data that were collected by using documentation. The data were analyzed by using content analysis and historical analysis. This findings demonstrate that according to Ibn Hazm, religious ethics are based on the Qurâ€™an and Hadith. It tends to solve the complication of â€œdialecticâ€ and focus on the effort in spreading the spirit of Islamic morality directly. This study also promote that several life problems that caused by globalization can be handled by using the principles of religious ethics offered by Ibn Hazm.